PEMBENTUKAN KARAKTER PADA ANAK: MODEL MEKANISME SANKSI DIRI DARI ALBERT BANDURA SEBAGAI REGULASI PERILAKU MORAL - Sri Lestari (Buletin Psikologi, 2009)
Child rearing in family has various purposes, among of them is to build child’s character. The evidence shows that character strengths are positively related to the individual’s well‐being and happiness. Albert Bandura proposed self‐sanction mechanism model to regulate moral behavior by giving physical sanction and verbal reprimand. As child grows, the child need parental guiding to understand standards of conduct and to learn about social sanction. If child can function self‐sanction mechanism, child is expected be able to evaluate his conduct right or wrong. The functioning of behavior moral regulation is an important part in developing child’s character. The strength and weakness of model and the application of this model in Indonesian context will be discussed.